2005
DOI: 10.1007/s11064-005-8654-x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Metabolizing Enzymes in Prefrontal Cortex of Alzheimer’s Disease Patients

Abstract: Amounts of glutamate metabolizing enzymes such as glutamate dehydrogenase (GDH), glutamine synthetase (GS), GS-like protein (GSLP), and phosphate-activated glutaminase (PAG) were compared in prefrontal cortex of control subjects and patients with Alzheimer disease (AD). The target proteins were quantified by ECL-Western immunoblotting in extracts from brain tissue prepared by two different techniques separating enzymes preferentially associated with cytoplasm (GDH I and II isoenzymes, GS, and partially GSLP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 27 publications
3
37
2
2
Order By: Relevance
“…Taken together, our study is the first to report unaltered serum GS concentrations in AD patients compared to age-matched control subjects and therefore suggests that there is no potential diagnostic value of serum GS for AD. This result is in contrast with some previous AD-related GS studies that found alterations of GS concentrations in serum [16], CSF [14,15] and brain tissue [4,5,17]. However, these studies did not share the same outcome as in serum and in CSF an increase of GS levels was found ( [16] and [15], respectively) whereas in brain tissue diverse outcomes were observed, with increases [17] but also with decreases [4,5] of reported GS levels.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Taken together, our study is the first to report unaltered serum GS concentrations in AD patients compared to age-matched control subjects and therefore suggests that there is no potential diagnostic value of serum GS for AD. This result is in contrast with some previous AD-related GS studies that found alterations of GS concentrations in serum [16], CSF [14,15] and brain tissue [4,5,17]. However, these studies did not share the same outcome as in serum and in CSF an increase of GS levels was found ( [16] and [15], respectively) whereas in brain tissue diverse outcomes were observed, with increases [17] but also with decreases [4,5] of reported GS levels.…”
Section: Discussioncontrasting
confidence: 97%
“…Also, Tumani et al [15] did not include age-matched controls but a control group with a wide variety of ages. Moreover, Burbaeva et al [17], Le Prince et al [5], Smith et al [4], Takahashi et al [16] and Tumani et al [15] included only 11, 8, 16, 24 and 8 AD patients, respectively. Most studies also included less control subjects, with exception of the study of Takahashi et al [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Определяли количество КФК В, исполь-зуя внутренний стандарт (образец мозга контрольной группы) [15] с помощью конъюгированных с пероксида-зой моноклональных мышиных антител в разведении 1:100 000. Антитела получены совместно с сотрудниками лаборатории клинической иммунологии ФГБНУ НЦПЗ.…”
Section: материал и методыunclassified
“…2 приведен пример окрашивания при ECL-иммуноблоттинге иммунореактивной КФК В во фрак-ции водорастворимых белков мозжечка. Видно, что ин-тенсивность окрашивания полосы, соответствующей КФК В, в контроле значительно выше (дорожки 1-9), чем у больных ШЗ (10)(11)(12)(13)(14)(15)(16)(17). Как и активность КФК, ко-личество иммунореактивной КФК В во всех анализиро-ванных областях мозга было значительно снижено у больных ШЗ по сравнению с контролем (во всех случаях р<0,01) (рис.…”
Section: количество иммунореактивной кфк в во фракции водорастворимыхunclassified